Advances in B Cell Targeting for Treating Muscle-Specific Tyrosine Kinase-Associated Myasthenia Gravis - Hu G; Zhao X; Wang Y; Zhu X; Sun Z; Yu X; Wang J; Liu Q; Zhang J; Zhang Y; Yang J; Chang T; et al. (ImmunoTargets and Therapy)
Guanlian Hu,1,2,* Xue Zhao,1,* Yiren Wang,1 Xiaoyan Zhu,1,3 Zhan Sun,1,2 Xiaoxiao Yu,1,2 Jiahui Wang,4 Qian Liu,1 Jing Zhang,1 Yingna Zhang,1 Junhong Yang,4 Ting Chang,5 Zhe Ruan,5 Jie Lv,1 Feng Gao1 1Department of Neuroimmunology, Henan Institute of Medical and Pharmaceutical Sciences, Zhengzhou University, Zhengzhou, People’s Republic of China; 2BGI College, Zhengzhou University, Zhengzhou, People’s Republic of China; 3Department of Neurology, The Second Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 4Department of Encephalopathy, First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, People’s Republic of China; 5Department of Neurology, Second Affiliated Hospital, Air Force Medical University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Gao; Jie Lv, Department of Neuroimmunology, Henan Institute of Medical and Pharmaceutical Sciences, Zhengzhou University, Zhengzhou, People’s Republic of China, Email gaoyuanshan@126.com; LJQ19972006@126.comAbstract: Myasthenia gravis (MG) is a typical autoimmune disease of the nervous system. It is characterized by skeletal muscle weakness and fatigue due to impaired neuromuscular junction transmission mediated by IgG autoantibodies. Muscle-specific receptor tyrosine kinase-associated MG (MuSK-MG), a rare and severe subtype of MG, is distinguished by the presence of anti-MuSK antibodies; it responds poorly to traditional therapies. Recent research on MuSK-MG treatment has focused on specific targeted therapies. Since B cells play a critical pathogenic role in producing autoantibodies and inflammatory mediators, they are often considered the preferred target for treating MuSK-MG. Currently, various B cell-targeted drugs have been developed to treat MuSK-MG; they have shown good therapeutic effects. This review explores the evolving landscape of B cell-targeted therapies in MuSK-MG, focusing on their mechanisms, efficacy, and safety, and the current limitations associated with their use. We discuss current B cell-targeted therapies aimed at depleting or modulating B cells via both direct and indirect approaches. Furthermore, we focus on novel and promising strategies such as Chimeric Autoantibody Receptor T cell therapy, which explicitly targets MuSK-specific B cells without compromising general humoral immunity. Finally, this review provides an outlook on the potential benefits and limitations of B cell-targeted therapy in developing new therapies for MuSK-MG. We conclude by discussing future research efforts needed to optimize these therapies, expand treatment options, and improve long-term outcomes in MuSK-MG management.Keywords: MuSK-MG, B cell-targeted therapy, direct targeting, indirect targeting, MuSK-CAR-T, MuSK-CAAR-T